Media Sosial Dan Transformasi Dakwah : (Analisis Intermedialitas Pada Konten Kajian Gus Baha) - Hasan Labiqul Aqil (Jurnal Ilmu Komunikasi, 2025)
The purpose of this study is to highlight the concept of intermediality as an analytical framework for understanding how Gus Baha’s da’wah messages adapt and interact in the digital age. Intermediality offers a relevant perspective in exploring the complexity and dynamics of media in contemporary culture, particularly in the context of the transformation of da’wah on social media. This study uses a qualitative approach with descriptive analysis methods to explore how Gus Baha’s study content interacts with audiences through social media dynamics. Intermediality in Gus Baha’s da’wah includes the use of various media that influence each other. Initially, his da’wah consisted only of audio recordings, then uploaded to YouTube with additional visuals. Klaus Bruhn Jensen identifies three concepts of intermediality: discursive, material, and institutional. Rajewsky offers three forms of intermediality: media transposition, media combination, and intermedial reference. This analysis shows how Gus Baha’s preaching utilizes digital media to convey religious messages effectively, creating adaptive and innovative communication in a modern context.